Estudo populacional de gambás, Didelphis Albiventris (Mammalia, Didelphidae), em um pequeno fragmento florestal - de Oliveira, Márcio L. [UNESP]; Ferreira, Rafael M. [UNESP]; Gomes, Marina P. [UNESP]; Iha, Danilo S. [UNESP]; Lorenzon, Cintia S. [UNESP]; Duarte, J. Maurício B. [UNESP] (My University, 2010)
The white-eared-opossums are habitat generalist animals and occur in high abundance in forest fragments. Therefore these animals are important to understand the dynamics of this landscape. The population of Didelphis albiventris in a 7 ha stational semidecidual forest fragment and its agricultural surroundings was studied during one year. The population abundance, age structure and sex ratio were estimated monthly. Two movements between the fragment and the surrounding area were detected. The population dynamics showed an annual pattern with a high peak during the dry season. © SAREM, 2010.
Population study of white-eared-opossum, Didelphis albiventris (Mammalia, Didelphidae), in a small forest fragment
Keywords: Atlantic forest; Capture-mark-recapture; Didelphis; Habitat fragmentation; Population ecology